The Stability Pact - Rationales, Problems, Alternatives - Assar Lindbeck; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2006)
We analyze economic rationales for, and possible alternatives to, the Stability and Growth Pact (SGP). We identify various cross-country spillover effects and domestic policy failures as potential rationales. The two sets of problems suggest different corrective measures, and different measures than those applied in the context of SGP. We contrast the "legalistic" perspective adopted in the Pact with a more incentive-based approach and discuss how the legalistic perspective gives rise to enforcement problems in connection with the implementa- tion of the SGP's sanctions.
Keywords: E63; F33; F42; H60; 330; Stability and Growth Pact; spillover effects; policy failures; Pigouvian taxes; enforcement of Stability Pact; Spillover-Effekt; Finanzpolitik; Geldpolitik; Internalisierung externer Effekte; Europäischer Stabilitätsmechanismus; Rechtsdurchsetzung